Role for plant foods in kidney health among middle-aged individuals environmentally exposed to cadmium and lead - Donrawee Waeyeng; Supabhorn Yimthiang; Phisit Pouyfung; Soisungwan Satarug; Tanaporn Khamphaya (PLoS ONE, 2026)
Plant food consumption has been associated with potential kidney health benefits; however, in polluted environments, such benefits may be diminished by exposure to toxic metals, notably, cadmium (Cd) and lead (Pb). Herein, plant food intake levels were investigated in relation to a simultaneous Cd/Pb exposure and kidney injury, reflected by urinary N-acetyl-β-D-glucosaminidase (uNAG). A cross-sectional study was conducted from October to December 2024 in southern Thailand, where ninety-six residents, aged ≥50 years were recruited during routine chronic disease screening. Consumption of plant foods was assessed using Plant Food Scores (PFS). Blood Cd and blood Pb levels were indicators of exposure to the metals. Estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN), urine creatinine, and uNAG were indicative of kidney function. ANOVA was used to compare PFS and kidney function indicators in Cd/Pb exposure groups, while associations of PFS, blood Cd, blood Pb and kidney function indicators were evaluated by multivariable regression. BUN levels rose in high Cd/Pb exposure group (12.64 to 15.79 mg/dL; p = 0.016), whereas eGFR and uNAG exhibited non-significant trends suggestive of renal stress. Total PFS was inversely associated with uNAG (β = −0.297; p = 0.010), and higher consumption of nuts and seeds was associated with a lower likelihood of elevated uNAG levels (OR = 0.185; 95% CI, 0.040–0.860; p = 0.032). Thus, consumption of plant foods, particularly nuts and seeds, was associated with lower levels of kidney tubular cell injury. ROC analysis showed good discriminatory ability for BUN (area under the curve [AUC] = 0.827) and uNAG (AUC = 0.813). Therefore, uNAG may have potential utility as a non-invasive biomarker of early renal tubular injury in populations chronically exposed to Cd/Pb.